Influence of micro-size titanium powders on mechanical properties of powder injection molded 316L stainless steel - Kashfi, Mohammadmahdi (Universiti Teknologi PETRONAS, 2017)
Powder injection molding (PIM) is a fast developing technology with significance of shape complexity, dimensional accuracy, replication fidelity and material variety combined with high-volume capabilities. To solve the challenge of producing materials with higher mechanical properties with the same or even lower weight, PIM can be consider a suitable technique; PIM enables us to enhance mechanical properties of base material by adding reinforcement powders. In this research the influence of micro-size titanium powders in enhancement of mechanical properties of stainless steel 316L SS is analyzed by producing samples with different volume percentage of titanium which include 0.2 Vol%, 0.8 Vol% and 1.5 Vol%. Moreover in this research the only variable remains the differences in compositions of feedstock, hence the process of sample production is unique for all three samples including binder system, feedstock preparation, injection molding, solvent debinding, thermal debinding and sintering.